Extração de alquilfenóis da casca, fenólicos da película e efeito do processamento industrial sobre constituintes da amêndoa de castanha de caju - Cavalcante, Jéfferson Malveira (2014)
The cashew nut is a major agro-industrial inputs, distinguishing as an icon in the economy northeast of Brazil. The cashew nut is made of almond (ACN), the main product, shell and testa, which have specific characteristics due to the presence of phenolic compounds. Of the present work the objective is to the evaluate the effects of industrial processing on constituents of almond, methods of extracting shell liquid (CNSL) and phenolic compounds in the testa. The extraction of CNSL was carried out following a full factorial design of experimental 3^2, varying pressure and temperature. The yield of pressing ranged from 26 to 34% in the extraction of CNSL with pressure and temperature exerting statistically significant positive effects. Occurred predominance the anacardic acids of C15:3, C15:2 and C15:1 in samples obtained by pressing and with the use of organic solvent, having a concentration in the range of 44-62% total anacardic acids. The extraction of phenolic compounds from the testa with water was performed following a rotational central composite design 3^2 by ultrasound-assisted extraction (UAE), varying the time, power density and liquid / solid ratio, and 2^2 for accelerated solvent extraction (ASE), varying time and temperature. The phenolic content extracted of the testa cashew nut using UAE ranged from 40-44% with SST ranging between 0.6 and 3.8, and between 33-46% for EAS and 1.5 to 4.3, respectively. The major phenolic compounds in the samples were catechin and epicatechin. The industrial processing steps of ACN were in nature, classified, humidified, cooked, dehydrated and selected, subjected to drying, grinding and lipid extraction. The humidity ranged between 2.5 and 11.0%, lipid had a mean value of 42%, except for the humidified ACN. The total anacardic acids, C15:3 and C15:1, had concentrations between 32 and 182 mg / g ACN oil and its degraded content and/or has been transformed from the incorporation of the seed during storage and humidification. The starch granules identified by the presence of the cross of Malta had rounded shapes and the amount decreased with the advance of industrial processing steps. The whole utilization the cashew with the extraction of the shell liquid cashew mini-factories because of its high content of alkylphenol in anacardic acids, together with the assistance of ultrasound and accelerated solvent extraction of phenolic compounds testa cashew nut proved attractive to the natural products market. The effect of industrial processing on constituents of almond cashew nut as anacardic acids directs to a reassessment process by the industry due to the large loss of alkylphenol content after the cooking step.